IMPLEMENTATION OF THE DERADICALIZATION PROGRAM FOR TERRORIST INMATES IN THE PROCESS OF PLEDGING ALLEGIANCE TO THE NATIONAL FLAG IN CLASS I CIPINANG PRISON - Putro, Jonathan Tri Anggoro; Biafri, Vivi Silviani (Universitas Nusa Cendana, 2025)
This article discusses the implementation of the deradicalization program for terrorist inmates in the process of pledging allegiance to the Republic of Indonesia at Cipinang Class I Correctional Institution, as well as identifying factors that hinder the effectiveness of the program. The results indicate that the implementation of the deradicalization program includes several stages, ranging from religious guidance to skills training to psychological counseling. However, this program has not been fully effective due to various obstacles. The main inhibiting factors include the lack of skills and special training for officers, officers' low interest in becoming Guardians of Terrorist Convicts, as well as limited resources and support from internal prison parties. In addition, the involvement of third parties such as clerics and psychologists often replaces the role of prison officers, who should be more active in the deradicalization process. This study recommends increased training and motivation for prison officers to strengthen the implementation of deradicalization programs more effectively and sustainably. Keywords: Deradicalization; Pledge of Allegiance; Terrorist Prisoners